Improving the performance of solar cells with novel buffer structure by the chemical bath deposition technique. (1st March 2017) - Ho, Jia-Show; Chang, Shih-Cheng; Ho, Jyh-Jier; Hsu, Wei-Tse; Chiang, Chien-Chih; Tsai, Song-Yeu; Wang, Sheng-Shih; Lin, Cheng-Kai; Chou, Chau-Chang; Yeh, Chi-Hsiao; Wang, Kang L.
Abstract: This paper explores and compares the characteristics of eight different kinds of Cu(In, Ga)Se2 (CIGS) solar cells. Through the technique of chemical bath deposition (CBD), single- (i-ZnO) and double-layer (ZnS/CdS) CIGS cells were prepared and evaluated. The results of this research signify the potential of high-performance CIGS cells for photovoltaic (PV) industrial applications. This study focused on the growth-dependency and optical properties of ZnS/CdS-buffer stacked thin films, which were prepared through the CBD process. The best sample developed from this process consisted of a double-layer buffer and no i-ZnO layer. This sample yielded a conversion efficiency (η) of 9.23% and a short-circuit current density (JSC ) of 26.72 mA/cm 2 . The performance of this sample was about 25% (absolute gain) better than that of the standard CdS cells. Furthermore, the average quantum efficiency in the short wavelength range (350–500 nm) for two of the ZnS/CdS buffer structures was 6.8% better than that of a single-layer CdS cell. This improvement can be attributed to the anti-reflective effect of the ZnS/CdS buffer structure, which increasesthe light-intensity incident on the main absorption layer. In addition, the ZnS/CdS-buffer layer not only eliminates the need for an i-ZnO layer but also reduces the usage of toxic Cd. The procedures to develop these flexible CIGS cells containing a ZnS/CdS buffer structure are simple, efficient, and reliable. These eco-friendly cells could be effectively applied to mass production for commercial PV applications. Highlights: We present a new structure to fabricate CIGS thin-film solar cells for better merits. The structure improves cost, conversion efficiency and reduces chemical pollution. The structure includes ZnS/CdS buffer with/without i-ZnO layers on the CIGS absorber. The beat features of η =9.23%, JSC=26.72 mA/cm2 and EQE for the short-wavelength range were improved. The optimal cell could be effectively and eco-friendly applied to commercial production